Obraz Boga w apoftegmatach ojców pustyni - Arkadiusz Nocoń (Vox Patrum, 2018)
It is often said today that the current religious crisis is caused by a false image of God. The question therefore is how is He to be presented, so that with all the limitations of the human intellect and language in the face of the apophatic character of the Divine Majesty, God will be expressed in a way that will be the least “detrimental” to Him (and also to man)? It seems that the Egyptian Desert Fathers may be qualified teachers, even masters in this matter, not only, because the “semblance of God” was an issue that greatly engaged their community which had to deal with the heresy of anthropomorphism, but even more so, because as men of deep faith and prayer, often great mystics, they had an experience of God and so they continue to be for us unrivalled “experts” in this field. Analysing therefore their teaching on the image of God contained in the Apophthegmata of the Desert Fathers, we have arrived at the following conclusions. The Desert Fathers were fully aware how important the image of God is in the process of faith, knowing that a false image may lead not only to personal tragedies, but even to social unrest, and that it always leads to an atrophy of prayer and is an obstacle on the way to perfection. In spite of this, even though the word “God” appears in the Apophthegmata very often, the search for some uniform image of God and even clauses of the type: “God is…” that are extremely rare, would be in vain. What could be the reasons for the “silence” of the Desert Fathers in this matter? In our view, first of all the fundamental reason was their humility and the fact that they did not see themselves as teachers of others, and second, their suspicion as to their own visions that could in fact hide the ruses of Satan. However, the most important reason for the “omission” of the image of God in the Apopthegmata is, in our view, Eastern spirituality which treated every endeavour to define God and to demonstrate His image as an attempt to limit His divine nature. The ineffable and infinite God in the understanding of the Desert Fathers was also a God who is unique and unspeakable, to such an extent that each individual has to arrive alone, in his own heart, as far as this is possible, at His true image. Thus, in the Apophthegmata we do not find univocal statements declaring what is the true image of God, and the only thing that the Desert Fathers have conveyed to us is that approaching God is something of a process, at the beginning of which, yes certainly, some even infantile imagination of God may be admissible (hence a “leniency” towards anthropomorphism), but then it has to be subjected to a progressive purification, in the knowledge that “that which is perfect will come later”. This will come, not so much as a result of hearing about God or the acquisition of knowledge about Him, but through the practice of prayer, pe-nance and almsgiving.